Measurement of the ratio of branching fractions B(B+c→J/[psi]K+)/B(B+c→J/[psi]π+) - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2016)
The ratio of branching fractions RK/π≡B(B+c→J/ψK+)/B(B+c→J/ψπ+) is measured with pp collision data collected by the LHCb experiment at centre-of-mass energies of 7 TeV and 8 TeV, corresponding to an integrated luminosity of 3 fb−1. It is found to be R K/π = 0.079 ± 0.007 ± 0.003, where the first uncertainty is statistical and the second is systematic. This measurement is consistent with the previous LHCb result, while the uncertainties are significantly reduced.
*The LHCb collaboration: R. Aaij, P. D'Argent, S. Bachmann, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, S. Esen, D. Gerick, E. Gersabeck, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kecke, M. Kolpin, K. Kreplin, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, S. Stemmle, U. Uwer, M. Vesterinen, A. Zhelezov [und sehr viele weitere Personen]
Im Titel ist das Zeichen + hochgestellt
Im Titel ist der Buchstabe c tiefgestellt
Im Titel ist "psi" als griechischer Buchstabe dargestellt
Gesehen am 07.07.2020